Dilemmas in the Management of Liminal Rodents—Attitudes of Dutch Pest Controllers - Maite A.A.M. van Gerwen; Joachim Nieuwland; Hein A. van Lith; Franck L.B. Meijboom (Animals, 2020)
When non-human animals are labeled as ‘pests’, their moral status and welfare seem relatively unimportant. In a multi-stakeholder project, we develop an assessment frame for a more responsible rodent management that includes animal welfare. An online survey among 129 Dutch pest controllers was carried out in order to find out more about pest controllers’ attitudes about animal welfare. Respondents indicate to consider animal welfare in their job. They see differences in the welfare impact of different rodent control methods. A dilemma may occur when methods with a high impact, such as rodenticides, are ofttimes used in practice. Respondents also indicate that in different real-life scenarios (the hospital kitchen vs. the private backyard), a different weight may be attributed to the importance of animal welfare. Almost half of the respondents encounter difficulties when weighing animals against human interests. The problems are mainly related to clients who are not willing to invest sufficient money in preventive methods, where respondents do believe in. Some differences were found between respondents depending on membership of a professional association for pest controllers. The results of this study are relevant input for focus groups with pest controllers and their clients and for the development of the aforementioned assessment frame.